Supercomputers, test ban treaties, and the virtual bomb. - Leitner, Peter M. (World Affairs)
The writer discusses the implications for nuclear test ban treaties of the development of high-performance computers. The proliferation of high-performance computers, made possible by the major liberalization of supercomputer export restraints unilaterally undertaken by the U.S. in 1995 and the illegal shipment by manufacturers, will serve to undermine the spirit and intent of the Comprehensive Test Ban Treaty (CTBT). Although the simulations provided by supercomputers are not a perfect replacement for the physical testing of nuclear weapons, they will provide an analytical platform for secret programs to achieve a higher level of confidence in their design, assembly, and detonation processes. Furthermore, the use of supercomputers could signify an end to transparency in nuclear testing, and the increased availability of supercomputers will likely contribute to nuclear proliferation. The writer concludes that the CTBT's value is in question if Russia was promised supercomputers to sign it and that the Senate should reject the treaty if this is shown to be the case.